2021
DOI: 10.31234/osf.io/t5wy9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mediating role of sensory differences in the relationship between autistic traits and internalizing problems

Abstract: Sensory processing abnormalities are common in autism spectrum disorder (ASD), and previous studies have shown a positive correlation between sensory processing and internalizing problems. This study examines the role of sensory processing abnormalities and difficulties resulting from sensory processing abnormalities on relationships between autistic traits and internalizing problems in Japanese female university students. One hundred and twelve female university students completed a questionnaire about their … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For instance, more social di culties were distinctly and speci cally linked to the presence of a local processing bias in non-clinical individuals (Russell-Smith et al, 2012). Other research showed that imagination di culties are speci c predictors of di culty in perceiving speech in noise in non-autistic individuals (Tsuji et al, 2024). Therefore, as autistic traits are heterogeneous in nature, it is crucial to not treat all autistic individuals as a homogenous group, and rather explore the shared as well as distinct characteristics of particular domains of autism using a psychometrically-sound multifactorial measure such as the AQ-28.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, more social di culties were distinctly and speci cally linked to the presence of a local processing bias in non-clinical individuals (Russell-Smith et al, 2012). Other research showed that imagination di culties are speci c predictors of di culty in perceiving speech in noise in non-autistic individuals (Tsuji et al, 2024). Therefore, as autistic traits are heterogeneous in nature, it is crucial to not treat all autistic individuals as a homogenous group, and rather explore the shared as well as distinct characteristics of particular domains of autism using a psychometrically-sound multifactorial measure such as the AQ-28.…”
Section: Discussionmentioning
confidence: 99%